Pola Komunikasi Antara Guru Dengan Siswa Dan Antar Siswa Pada Kelompok Ekstrakurikuler TariDi Smp N 1 Delanggu(Studi Deskriptif Kualitatif Pola Komunikasi Antara Guru Dengan Siswa DanAntar Siswa Pada Kelompok Ekstrakurikuler Tari Di Smp N 1 Delanggu - Astuti, Sekartaji Reni; , Drs. Joko Sutarso, S.E, M.Si (2017)
The purpose of the research is to describe patterns of ommunication betweenteachers and students and among students in dance extracurricular group in SMP N1 Delanggu. The object of research is a student and teacher at SMP N 1 Delangguwhich involved in extracurricular activities. The method in this research usedescriptive study. Collecting data using in-depth interviews, observation nddocumentation. The validity of the data using triangulation of sources and techniques. The research analysis using interactiveanalysis. The results of thisstudy were: 1) patterns of communication between teachers and students is thecommunications quivalent but manners: (a) the teacher put himself as a friend of students, (b) the students feel comfortable with the teacher, (c) and the studentswere still being polite with teachers who have power value, as teachers or coaches in extracurricular dance is a facilitator be friendly and became friends in learning,making students feel comfortable and consider the teacher as a friend but also still respect the teachers; 2) patterns of communication between students in the groupextracurricular dance is symmetrical communication: a) have the same power, b)2occurs convenient communications group, and c) solidarity in learning the dance sothat students feel comfortable with other friends so as to make activitiesextracurricular dance more fun and friends.Keywords: Interpersonal communication patterns, teacher, student,extracurricular, dance